Mothers' experiences of reducing family mealtime screen use in Australian households with young children - Eloise-Kate Litterbach; Rachel Laws; Miaobing Zheng; Karen J Campbell; Alison C Spence (Cambridge University Press, 2024)
Abstract Objective: Screen use at mealtimes is associated with poor dietary and psychosocial outcomes in children and is disproportionately prevalent among families of low socio-economic position (SEP). This study aimed to explore experiences of reducing mealtime screen use in mothers of low SEP with young children. Design: Motivational interviews, conducted via Zoom or telephone, addressed barriers and facilitators to reducing mealtime screen use. Following motivational interviews, participants co-designed mealtime screen use reduction strategies and trialled these for 3-4 weeks. Follow-up semi-structured interviews then explored maternal experiences of implementing strategies, including successes and difficulties. Transcripts were analysed thematically. Setting: Australia. Participants: Fourteen mothers who had no university education and a child between six months and six years old. Results: A range of strategies aimed to reduce mealtime screen use were co-designed. The most widely used strategies included changing mealtime location and parental modelling of expected behaviours. Experiences were influenced by mothers' levels of parenting self-efficacy and mealtime consistency, included changes to mealtime foods and an increased value of mealtimes. Experiences were reportedly easier, more beneficial and offered more opportunities for family communication, than anticipated. Change required considerable effort. However, effort decreased with consistency. Conclusions: The diverse strategies co-designed by mothers highlight the importance of understanding why families engage in mealtime screen use and providing tailored advice for reduction. Although promising themes were identified, in this motivated sample, changing established mealtime screen use habits still required substantial effort. Embedding screen-free mealtime messaging into nutrition promotion from the inception of eating will be important.